Metodologi Takhrīj Berdasarkan Tema Hadis Serta Contoh Aplikatifnya - Sudarmin, Sudarmin; Muhammad Ali; M. Asyraf Mubarak Sudarmin (JAWAMI'UL KALIM: Jurnal Kajian Hadis, 2024)
Hadith is the second source of Islamic teachings after the Qur'an. Many times the hadiths found in the community are incomplete, whether the text of the hadith is only a piece or incomplete, the sanad is incomplete and even the original source is unknown. Therefore, it is necessary to learn the takhrīj of hadith. Takhrīj hadis consists of five methods, but in this paper only focuses on the fourth method or the one based on the theme of the hadith. this research is a literature review using descriptive qualitative methods. This study is a literature review using descriptive qualitative method. This paper seeks to explain matters related to the takhrij hadith, especially the takhrij method based on the theme of the hadith, and to provide an example of its application.